preparation and characterization of high methanol resistance sulfonated poly (ether ketone)membrane for DMFC application - Juhana Jaafar, 1981-, author; Ahmad Fauzi Ismail, 1966-, author; Regional Symposium on Membrane Science and Technology (6th: 2008: Thailand) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL